Financial Control Tools in Light of the Reforms of Organic Law 15-18 - Khalil, Wahid; Guaoui, Said (Journal of Legal Studies and Researches, 2023)
Financial oversight of public funds is one of the most important axes on which financial and budgetary reforms are focused, led by organic law 15-18 related to the following laws, whether through strengthening parliamentary oversight of financial laws, in their various stages of maturity from preparation to discussion and voting.